Routledge Handbook of Asian Transnationalism - Sahoo, Ajaya Kumar (Taylor & Francis, 2023)
"This handbook presents cutting-edge research on Asian transnationalism written by experts in the areas of migration, diaspora, ethnicity, gender, language, education, politics, media, art, popular culture, and literature from a diverse theoretical and methodological perspectives. The Asian region not only constitutes one of the largest diasporic populations in the world but also the most diversified diasporas in terms of their historical trajectories of emigration, geographical spread, economic and political strength, socio-cultural integration in the host country, and transnational engagement with the homeland. Divided thematically into six broad sections the chapters in this handbook critically discuss and debate some of the pertinent issues of Asian transnationalism: • Contextualizing Asian Transnationalism • Transnationalism and Socio-Cultural Identities • Transnationalism, Education, and Infrastructure • Transnationalism, Gender, and Development • Transnationalism and Dynamics of Diasporic Politics • Transnationalism, Art, and Media The Routledge Handbook of Asian Transnationalism will be an invaluable resource for academics, researchers, and students interested in the study of international migration, Asian diaspora, and transnationalism. "